2018
DOI: 10.31234/osf.io/cw9qs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Study of Microdosing Psychedelics

Abstract: The phenomenon of ‘microdosing’, that is, regular ingestion of very small quantities of psychedelic substances, has seen a rapid explosion of popularity in recent years. Individuals who microdose report minimal acute effects from these substances yet claim a range of long-term general health and wellbeing benefits. There have been no published empirical studies of microdosing and the current legal and bureaucratic climate makes direct empirical investigation of the effects of psychedelics difficult. In Study O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…161 component, which is suggested to be crucial for their therapeutic potential. 163 The use of psychedelic microdosing to boost creativity and productivity whilst limiting opportunities for profound insights to inspire change 164 exemplifies how the substances can be used to reinforce neoliberal values. Additionally, the rise of microdosing or short retreats demonstrate how the administration of commercialized psychedelics is often in a form which is designed to provide a quick fix, rather than putting in the necessary preparation or integration required to deliver transformative experiences and acknowledge the importance of the right set and setting.…”
Section: Discussionmentioning
confidence: 99%
“…161 component, which is suggested to be crucial for their therapeutic potential. 163 The use of psychedelic microdosing to boost creativity and productivity whilst limiting opportunities for profound insights to inspire change 164 exemplifies how the substances can be used to reinforce neoliberal values. Additionally, the rise of microdosing or short retreats demonstrate how the administration of commercialized psychedelics is often in a form which is designed to provide a quick fix, rather than putting in the necessary preparation or integration required to deliver transformative experiences and acknowledge the importance of the right set and setting.…”
Section: Discussionmentioning
confidence: 99%
“…Psilocybin at microdoses also requires more rigorous investigation. A recent systematic study found microdosing improves mood, energy levels and cognition, creativity, optimism and openness, as well as alters perceptions of time (Polito & Stevenson, 2019) and a recent self-report study of microdosers found reductions in depression, stress and distractibility with increased absorption and neuroticism (Anderson, et al, 2019). Smaller sub-perceptual doses would allow for more relaxed trial inclusion criteria, and could be possibly be used in the treatment of PTSD given the role of low-dose psilocybin in reducing fear response in laboratory animals (Catlow et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Due to technical limitations, our LC-MS method may not be sensitive enough to detect brain or plasma concentrations of (2R,6R)-HNK within the picogram range, and future studies may have more success using accelerated mass spectrometry (39,40). Although, to our knowledge, these microdoses of (R,S)-ketamine and its metabolites have not previously been studied, there has been a recent resurgence in examining the potential benefit of microdosing, in which small quantities of psychedelic substances are repeatedly ingested (39)(40)(41)(42)(43)(44)(45)(46)(47). This unique method of administration is reported to exert a myriad range of benefits, including improved mood, heightened creativity, and increased focus, without inducing nonspecific psychotropic or addictive side effects (43,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Although, to our knowledge, these microdoses of (R,S)-ketamine and its metabolites have not previously been studied, there has been a recent resurgence in examining the potential benefit of microdosing, in which small quantities of psychedelic substances are repeatedly ingested (39)(40)(41)(42)(43)(44)(45)(46)(47). This unique method of administration is reported to exert a myriad range of benefits, including improved mood, heightened creativity, and increased focus, without inducing nonspecific psychotropic or addictive side effects (43,46,47). Moreover, evidence suggests that studying microdosing at the preclinical stage may lead to more reliable predictions of the pharmacokinetics in human populations (41,42,44,45).…”
Section: Discussionmentioning
confidence: 99%